Implementation of State Civil Apparatus Data Information System at BKPSDMD Makassar City - Sulmiah, Sulmiah; Guntur, Muhammad; Amin, Siti Alfianty Astini; Purna, Zarni Adia (Jurnal Aktor, 2024)
This paper aims to determine the Implementation of Digital Archives in Supporting Accountability of Accountable ASN Data in the Information System at the BKPSDMD Makassar City. This research uses a qualitative approach and produces descriptive data. Data collection is done by observation, interviews and documentation. Data is processed using interactive model analysis, namely data condensation, data presentation and conclusion testing. The results showed that the implementation of the State Civil Apparatus (ASN) data information system at the Makassar City BKPSDMD in this case regarding digital archives has been implemented but is still not optimal. There are 4 indicators that are taken into consideration in looking at the implementation of the policy, namely in terms of communication, resources, disposition and bureaucratic structure. Of the four indicators, the obstacles in implementing and implementing digital archives are resources because first, the availability of staff within the scope of the BKPSDMD Makassar City is still very lacking and indeed until now there are several contract and honorary workers employed at the BKPSDMD Makassar City Office because of the many jobs that are the main duties and functions of employees,  and secondly regarding the facilities and infrastructure in the BKPSDMD Makassar City office is still very minimal due to the lack of supporting devices in applying digital archives for staff and complete equipment is only provided in certain parts.